Feeling How Old I Am: Subjective Age Is Associated With Estimated Brain Age - Kwak, Seyul; Kim, Hairin; Chey, Jeanyung; Youm, Yoosik (Frontiers in Aging Neuroscience, 2018)
While the aging process is a universal phenomenon, people perceive and experience one’s aging considerably differently. Subjective age, referring to how individuals experience themselves as younger or older than their actual age, has been highlighted as an important predictor of late-life health outcomes. However, it is unclear whether and how subjective age is associated with the neurobiological process of aging. In this study, 68 healthy older adults underwent a subjective age survey and magnetic resonance imaging scans. T1-weighted brain images of open-access datasets were utilized to construct a model for age prediction. We utilized both voxel-based morphometry and age-prediction modeling techniques to explore whether the three groups of subjective age (i.e., feels younger, same, or older than actual age) differed in their regional gray matter volumes, and predicted brain age. The results showed that elderly individuals who perceived themselves as younger than their real age showed not only larger gray matter volume in the inferior frontal gyrus and the superior temporal gyrus, but also younger predicted brain age. Our findings suggest that subjective experience of aging is closely related to the process of brain aging and underscores the neurobiological mechanisms of subjective age as an important marker of late-life neurocognitive health.